Витоки та перші спроби застосування інституту національно-культурної автономії - Оніщенко, К.О. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья посвящена эволюции института национально-культурной автономии. Исследуются истоки национально-культурной автономии в теории австромарксистов Австро-венгерской империи. Особое внимание уделяется роли, которою должен был сыграть институт экстерриториальной автономии, а именно предотвратить развал страны. Также исследуется попытки внедрения модели национально-культурной автономии в УНР. An article is devoted to personal autonomy institute. The roots of personal autonomy are investigated in Austrian Marxist theory. The closest attention is paid to the role of personal autonomy institute, which it had to play in Austria-Hungary, precisely to prevent country's disintegration. The attempts of personal autonomy model implementation in UNR is investigated as well.